Simulation and performance of space time frequency coding by using turbo code / Ismail Ibrahim - Ibrahim, Ismail (2008)
This project highlights the simulation using Space Time Frequency Coding (STFC) in order to identify the performance capability of Turbo Code with using a Quaternary Phase Shift Keying (QPSK) modulation technique. Generally, Turbo Code as encoder is functioning to convert the input signal become into a binary form before the modulation happens. The project report focuses on the simulation by the Matlab software. Upon this report, the performance of Turbo Codes as an encoder at the transmitter, and decoder at the receiver by using Space Time Frequency Code (STFC). Matlab Version 7.5 is used to simulate the system. The model consists of transmitter, transmission channel and receiver.